2020
DOI: 10.3390/nu12103196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Status during Pregnancy on Infant Neurodevelopment: The ECLIPSES Study

Abstract: Vitamin D status during pregnancy is involved in numerous physiological processes, including brain development. In this study, we assess the association between vitamin D status during pregnancy and infant neurodevelopment (cognitive, language, and motor skills). From an initial sample of 793 women (mean age 30.6) recruited before the 12th week of pregnancy, 422 mother–infant pairs were followed up to a postpartum visit. Vitamin D levels were assessed in the first and third trimesters of pregnancy, and socio-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 39 publications
0
34
0
1
Order By: Relevance
“…However, some other studies have not found associations between vitamin D and cognitive ability [16][17][18][19] or scholastic achievement [20] in school-aged children. Furthermore, a number of studies have examined developmental and cognitive outcomes in babies and toddlers with mixed findings [21][22][23]. The current evidence supports vitamin D supplementation during pregnancy to prevent gestational diabetes and low birthweight in offspring [24], but evidence is limited on the benefits of supplementation on cognitive outcomes in offspring [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, some other studies have not found associations between vitamin D and cognitive ability [16][17][18][19] or scholastic achievement [20] in school-aged children. Furthermore, a number of studies have examined developmental and cognitive outcomes in babies and toddlers with mixed findings [21][22][23]. The current evidence supports vitamin D supplementation during pregnancy to prevent gestational diabetes and low birthweight in offspring [24], but evidence is limited on the benefits of supplementation on cognitive outcomes in offspring [25].…”
Section: Introductionmentioning
confidence: 99%
“…[ 52 ] Detailed information on laboratory procedures for PUFA measurements can be found in Aparicio et al [ 53 ] Serum concentrations of vitamin D were quantified by an automated chemiluminescent immunoassay method as described in Díaz-López et al [ 54 ] The rationale for including serum concentrations of vitamin D and fatty acids in the analyses is that these components are involved in brain development, so maternal levels during pregnancy may influence foetal neurodevelopment. [ 55 57 ] Folate and vitamin B 12 measurements were also done by using a chemiluminescence immunoassay only in the first trimester of gestation. Then, RBC folate concentration was calculated as follows: (serum folate in haemolysed whole blood * dilution factor in haemolysis * 100)/haematocrit.…”
Section: Methodsmentioning
confidence: 99%
“…19 Vitamin D plays a role in neuronal proliferation, differentiation, neurotransmission, neuroplasticity, neuroprotection, and myelination, according to data from in vitro, ex vivo, and animal models. 20 This is further reinforced by the fact that vitamin D levels are linked to the levels of many neurotrophic factors, including nerve growth factors (NGFs) and those of neurotrophins, both of which are essential for the maintenance and the growth of neurons. 21 With the advancement of research, vitamin D has been related to cognitive dysfunction, psychosis, and autism in the interchange of decreased vitamin D levels.…”
Section: Ironmentioning
confidence: 99%
“…In specific, vitamin D deficiency in the first trimester of pregnancy predicted worse performance in cognitive and language skills, while during the third trimester, this deficiency affected motor development. 20 According to a recent study on the effect of vitamin D supplementation in the treatment of children with autism spectrum disorders, oxidative stress and mitochondrial dysfunction are common in individuals with autism spectrum disorders, and vitamin D acts as a counterprotective mechanism by protecting the genome from oxidative stress and DNA damage and the regulation of cellular proliferation and differentiation. 22 Choline Chemically, choline is closely related to the Bvitamin family.…”
Section: Ironmentioning
confidence: 99%